2022
DOI: 10.1101/2022.04.13.488148
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of Long-Short Term Memory Networks for M/EEG Source Imaging with Simulated and Real EEG Data

Abstract: Magneto- and electroencephalography (M/EEG) are widespread techniques to measure neural activity in vivo at a high temporal resolution but relatively low spatial resolution. Locating the sources underlying the M/EEG poses an inverse problem, which is itself ill-posed. In recent years, a new class of source imaging methods was developed based on artificial neural networks. We present a long-short term memory (LSTM) network to solve the M/EEG inverse problem. It integrates several aspects essential for qualitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 83 publications
(127 reference statements)
0
5
0
Order By: Relevance
“…As we have shown in this work, combining FLEX-MUSIC and a Champagne algorithm may be useful, although Champagne may overestimate the size of neural sources in some cases. An interesting family of recently developed inverse solution are based on artificial neural networks (ANNs, Hecker et al, 2020Hecker et al, , 2022. In a next step we plan to compare a potentially further optimized version of FLEX-MUSIC with this family of ANN-based solvers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As we have shown in this work, combining FLEX-MUSIC and a Champagne algorithm may be useful, although Champagne may overestimate the size of neural sources in some cases. An interesting family of recently developed inverse solution are based on artificial neural networks (ANNs, Hecker et al, 2020Hecker et al, , 2022. In a next step we plan to compare a potentially further optimized version of FLEX-MUSIC with this family of ANN-based solvers.…”
Section: Discussionmentioning
confidence: 99%
“…A novel class of inverse solvers arose in the past decade that utilize the recent advances in machine learning, predominantly artificial neural networks (ANNs) to solve M/EEG inverse problems. These approaches require training an ANN to produce a source estimate based on simulated pairs of source and M/EEG activity and achieve high accuracy compared to many conventional methods (Cui et al, 2019; Hecker, Rupprecht, van Elst, & Kornmeier, 2020, 2022; Pantazis & Adler, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Neural sources underlying the ERPs were calculated using a fully-connected ANN, which has shown to yield accurate inverse solutions with respect to source location and estimation of source extent [31,13]. We used simulated neural sources and scalp EEG data to train the fully-connected (FC) ANN model.…”
Section: Artificial Neural Network (Ann)mentioning
confidence: 99%
“…We found that the SNR of our participants ranged from 4.2 -19.9, which was again used as the parameter range for the simulation. For further details on the simulation procedure please refer to [13].…”
Section: Artificial Neural Network (Ann)mentioning
confidence: 99%
“…A novel class of inverse solvers arose in the past decade that utilize the recent advances in machine learning, predominantly artificial neural networks (ANNs) to solve M/EEG inverse problems. These approaches require training an ANN to produce a source estimate based on simulated pairs of source and M/EEG activity and achieve high accuracy compared to many conventional methods (Cui et al, 2019 ; Hecker et al, 2020 , 2022 ; Pantazis and Adler, 2021 ). ANNs are prone to biases in the training data, wherefore their application is yet limited.…”
Section: Introductionmentioning
confidence: 99%